A Biologic and Physical Characterization of an Injectable Amniotic Membrane Designed for Treating Diabetic Foot Ulcers - Kimberly Velarde; Audrey Arvonen; Tatyana Gonzalez; Robert B. Diller (Bioengineering)
Introduction: Globally, the health and quality of life of millions of people are negatively affected by diabetic foot ulcers (DFUs). To treat these chronic wounds, a novel injectable drug for closing DFUs composed of micronized amniotic membrane was developed. This new therapeutic drug for wound repair expands on traditional allograft therapies by allowing extracellular matrix proteins, growth factors, and cytokines to reach wound anatomies in DFUs that are difficult to treat. The aim of this study was to evaluate the components of the injectable drug. Methods: Liquid chromatography with tandem mass spectrometry and a Quantibody® human cytokine array were conducted to identify and characterize growth factors and proteins known to contribute to wound healing. In addition, hyaluronic acid was quantified and compared between the injectable and human amniotic fluid using a hyaluronan enzyme-linked immunosorbent assay. Cell proliferation, migration, angiogenesis, and viability were evaluated to assess the performance of the novel injectable in vitro. The rheometric properties of the product were evaluated by assessing it pre- and post-injection through a 22-gauge needle to measure the viscosity using a shear- and temperature-dependent viscosity protocol. Results: Liquid chromatography with tandem mass spectrometry and Quantibody® human cytokine array revealed growth factors and proteins imperative for wound healing. The quantified hyaluronic acid was compared between the injectable and human amniotic fluid, resulting in a statistically significant difference, with higher protein concentrations found in the injectable. In vitro qualitative and quantitative analysis confirmed an increase in cell viability, proliferation, and migration when treated with the drug. An evaluation of the rheometric properties of the injectable drug after passing through a 22-gauge cannula presented no alterations to the biologic drug. Conclusions: Collectively, these data present the potential of a novel injectable drug for the treatment of DFUs.